Analisis Peran Fintech Syariah dalam Meningkatkan Keuangan Inklusif pada UMKM Kota Medan - Ahmad Riadi Rangkuti; Nurbaiti; Mawaddah Irham (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstract financial technology or financial technology is the use of technology in the financial system that produces products, services, technology and/or business models and can have an impact on monetary stability, financial system stability, efficiency, smoothness, security and reliability of the payment system. Fintech is an innovation in the financial services industry that utilizes the use of technology. Meanwhile, Sharia Fintech is a financial service or product that uses technology based on a sharia scheme. This study aims to determine the role of Fintech in increasing financial inclusion in UMKM in Medan City. What are the obstacles in implementing Fintech in increasing inclusive finance for UMKM in Medan City, and what are the risks of implementing Fintech in increasing inclusive finance for UMKM in Medan City. The type of data used in this study is qualitative data while the data sources are primary data and secondary data. The data collection method in this study was carried out using interviews, documentation and literature study. From the results of data analysis which can then be drawn conclusions. This research was conducted by giving a series of questions to the owner of Siti Khadijah's Warung Qu and Batik Business. Based on the research results, the researcher draws the conclusion that the role of fintech for UMKM is in the form of ease of transactions, with Fintech transactions at this time are faster, safer, easier and more reliable besides that fintech also has financial regulatory features that aim to make it easier for UMKM to manage their finances. One of the implementations of Fintech is human resources (HR) who still don't understand technology. The risk of implementing Fintech for MSMEs is the occurrence of online crimes or known as cyber cream, such as fraud and account theft. Keywords: Fintech, Inclusive Finance, UMKM